Are we allowed to visit now? Concerns and issues surrounding vaccination and infection risks in UK care homes during COVID-19. (25th November 2021) - Giebel, Clarissa; Hanna, Kerry; Cannon, Jacqueline; Marlow, Paul; Tetlow, Hilary; Mason, Stephen; Shenton, Justine; Rajagopal, Manoj; Gabbay, Mark
Abstract: Background: vaccination uptake in the UK and increased care home testing are likely affecting care home visitation. With scant scientific evidence to date, the aim of this longitudinal qualitative study was to explore the impact of both (vaccination and testing) on the conduct and experiences of care home visits. Methods: family carers of care home residents with dementia and care home staff from across the UK took part in baseline (October/November 2020) and follow-up interviews (March 2021). Public advisers were involved in all elements of the research. Data were analysed using thematic analysis. Results: across 62 baseline and follow-up interviews with family carers ( n  = 26; 11) and care home staff ( n  = 16; 9), five core themes were developed: delayed and inconsistent offers of face-to-face visits; procedures and facilitation of visits; variable uptake of the COVID-19 vaccine; misinformation, education and free choice; frustration and anger among family carers. The variable uptake in staff, compared to family carers, was a key factor seemingly influencing visitation, with a lack of clear guidance leading care homes to implement infection control measures and visitation rights differently. Conclusions: we make five recommendations in this paper to enable improved care home visitation in the ongoing, and in future, pandemics. Visits need to be enabled and any changes to visiting rights must be used as a last resort, reviewed regularly in consultation with residents and carers and restored as soon as possible as a top priority, whilst more education needs to be provided surrounding vaccination for care home staff.